2017
DOI: 10.1038/s41431-017-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular issues of KMT2A variants involved in Wiedemann-Steiner syndrome

Abstract: Variants in KMT2A, encoding the histone methyltransferase KMT2A, are a growing cause of intellectual disability (ID). Up to now, the majority of KMT2A variants are non-sense and frameshift variants causing a typical form of Wiedemann-Steiner syndrome. We studied KMT2A gene in a cohort of 200 patients with unexplained syndromic and non-syndromic ID and identified four novel variants, one splice and three missense variants, possibly deleterious. We used primary cells from the patients and molecular approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…The predominant findings were vertebral segmentation defects (9/11), involving different cervical vertebrae and various degrees of fusion of the vertebral bodies and/or posterior elements. The most common was cervical C2/C3 vertebral fusion (7/11), also reported in Baer et al, 2018 andLebrun et al, 2018; one individual had a more severe C1/C2 vertebral fusion, while another had a combination of C2/C3 and C1/occiput fusion.…”
Section: Cvj Anomalies Of the 11 Participantsmentioning
confidence: 78%
See 1 more Smart Citation
“…The predominant findings were vertebral segmentation defects (9/11), involving different cervical vertebrae and various degrees of fusion of the vertebral bodies and/or posterior elements. The most common was cervical C2/C3 vertebral fusion (7/11), also reported in Baer et al, 2018 andLebrun et al, 2018; one individual had a more severe C1/C2 vertebral fusion, while another had a combination of C2/C3 and C1/occiput fusion.…”
Section: Cvj Anomalies Of the 11 Participantsmentioning
confidence: 78%
“…We have recently resolved the diagnosis of a patient who, in addition to typical WDSTS features, presented with cervical C2/C3 vertebral fusion and small foramen magnum. At the same time, anomalies of the craniovertebral junction (CVJ) have been reported in a few other WDSTS patients (Baer et al, 2018;Feldman, Dlouhy, Lah, Payne, & Weaver, 2019;Lebrun et al, 2018), suggesting that they may warrant inclusion among the WDSTS-associated features.…”
mentioning
confidence: 99%
“…Other 5 recurrent variants, including p.Arg1154Trp [ 11 ], p.Cys1155Tyr [ 11 , 22 ], p.Gly1168Asp [14, this study], p.Arg1633* [ 2 , 11 ] and p.Arg2480* [ 7 , 11 ] were also identified. Although we did not find hotspot variation region, it is noteworthy that only missense variants (7/17) occurred in the cysteine-rich CXXC zinc finger domain (Additional file 2 : Table S2), which is predicted to selectively bind to unmethylated CpG-containing stretches of the target genes [ 10 ]. Previous studies suggested that patients who harbor the missense variant in the CXXC DNA binding domain may show more severe neurodevelopmental delay [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find hotspot variation region, it is noteworthy that only missense variants (7/17) occurred in the cysteine-rich CXXC zinc finger domain (Additional file 2 : Table S2), which is predicted to selectively bind to unmethylated CpG-containing stretches of the target genes [ 10 ]. Previous studies suggested that patients who harbor the missense variant in the CXXC DNA binding domain may show more severe neurodevelopmental delay [ 10 , 14 ]. Indeed, in our cohort, Patient 5 (p.Gly1168Asp) has the most severe anomalies in neurological development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation